Estimation of Growth Parameters Using Length Frequency Data of Whiting (Merlangius merlangus euxinus, Nordmann 1840), from Black Sea Coasts of Turkey - Hakan Aksu (Journal of New Results in Science)
Abstract: The growth parameters of whiting (M. merlangus euxinus, N. 1840) were estimated using length frequency data collected by trawl fishing in the Sinop region, Turkey during September 2009 to April 2010. A total of 7716 whiting were sampled monthly, ranging from 3.2 to 26.6 cm in total length (mean 14.09±0.03 cm). The Length-Weight relation calculated that W=0.0047 L 3.1694 (r2 =0.97) for females and W=0.0058 L 3.077 (r2 =0.96) for males. The regression coefficient "b" exhibit positive allometric growth (p<0.05, t= 2.91) for females and isometric growth (p>0.05, t= 1.75) for males. The mean condition factor (K) for females and males was determined 0.74±0.0046 and 0.71±0.0038, respectively. The highest condition factor was recorded 0.99 in October for females and 0.88 in January for males. The seasonal von Bertalanffy growth parameters using monthly length frequency distributions were estimated as L∞ = 20.10 cm TL, K = 0.652 year-1, t0 = -0.850 for all individuals. The time of the slowest growth period were determined in September (WP = 0.71). A growth performance index value (Φ’) was estimated as 2.4205.